Species-wide gene editing of a flowering regulator reveals hidden phenotypic variation. - Ulrich Lutz; Ilja Bezrukov; Rebecca Schwab; Wei Yuan; Marius Kollmar; Detlef Weigel (PLoS Biology)
Genes do not act in isolation, and the effects of a specific variant at one locus can often be greatly modified by polymorphic variants at other loci. A good example is FLOWERING LOCUS C (FLC), which has been inferred to explain much of the flowering time variation in Arabidopsis thaliana. We use a set of 62 flc species-wide mutants to document pleiotropic, genotype-dependent effects for FLC on flowering as well as several other traits. Time to flowering was greatly reduced in all mutants, with the remaining variation explained mainly by allelic variation at the FLC target FT. Analysis of FT sequence variation suggested that extremely early combinations of FLC and FT alleles should exist in the wild, which we confirmed by targeted collections. Our study provides a proof of concept on how pan-genetic analysis of hub genes can reveal the true extent of genetic networks in a species.